Development of Early Detection Instruments of Building Intention in Elementary School Students - Vinayastri, Amelia; Tjalla, Awaluddin; Arthur , Riyan (Technium Social Sciences Journal, 2023)
Bullying in childhood is very detrimental and has a negative impact both in the short and long term. Bullying can cause stress, decreased self-esteem, difficulty getting along, causing psychosocial problems such as depression, loneliness, and anxiety, triggering somatic symptoms, low academic achievement, dropping out of school, increasing psychosis, and encouraging suicidal ideation. Bullying must be prevented and reduced through various efforts such as bullying prevention programs, namely detection and intervention against bullying. In order to detect the potential for bullying to occur, this research focuses on producing instruments for the early detection of child bullying intentions in elementary school students. The instrument developed was an early detection questionnaire on child bullying intentions (DDIPA). The study involved 1260 elementary school students in the early grades. Data analysis using Rasch modeling. The result is a DDIPA instrument consisting of 39 valid and reliable statement items. The DDIPA instrument can be used by researchers, teachers, and counselors in order to detect potential bullying in schools.